DEVELOPMENT OF A PROJECT LEARNING LEARNING MODEL TO IMPROVE THE CRITICAL AND CREATIVE THINKING ABILITY OF ELEMENTARY SCHOOL STUDENTS IN THE WETLAND AREA OF BARITO KUALA REGENCY - Sari, Raihanah; Arisanty, Deasy; Angriani, Parida (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
This research is motivated by the demands of the 21st century, which require students to have communication, collaboration, critical thinking, problem-solving, and innovation skills. One of the skills that is quite important for students to have is critical and creative thinking. Educators must find a breakthrough in the learning process to improve students' critical and creative thinking abilities. The learning models currently used at the elementary school level are still incapable of developing students' critical and creative thinking abilities, so there is a need for innovative learning models that can provide opportunities for students to develop their thinking abilities. The project learning model, a combination of PBL and PJBL, is an answer to a model that can be used to develop elementary school students' critical and creative thinking abilities. This type of research is development intended to obtain a product. The research stages can be detailed as follows: (1) the pre-field stage or preparation stage, (2) the advanced stage, developing the Project Learning learning model, and (3) the post-field stage, where the research team prepares a report. This research activity begins with basic research regarding the learning model that has been used by teachers in elementary schools in the Wetlands area of ​​​​Barito Kuala Regency, then continues with the stages of developing the Project Learning learning model, which is a solution for improving students ' critical and creative thinking abilities.